A study on summer monsoon season and rainfall characteristics in summer monsoon season over Southern Vietnam in 1981-2014 period - Ngo-Thi-Thanh, Huong; Vu-Thanh, Hang (Vietnam Journal of Marine Science and Technology, 2017)
This study determines the summer monsoon season over Southern Vietnam in 1981-2014 period by using observed daily rain-gauge data and reanalyzed daily 850 hPa wind data. The results show that the mean onset and retreat dates of summer monsoon over Southern Vietnam occur on May 15 and October 13, with standard deviations of 14.12 and 13.55 days, respectively. The results also show that the onset and retreat dates tend to precede in the recent years. In summer monsoon period, the values of RX1day and RX5day are high in Rach Gia and Ca Mau but low in Can Tho, CDD of all stations are low. In all stations, the values of extreme rainfall indices in 1998-2014 period are higher compared to those in 1981-1997 period